PENGUATAN LITERASI KEAMANAN DIGITAL MELALUI IMPLEMENTASI SISTEM AUTENTIKASI GANDA PADA PENGGUNAAN E-MONEY - Mikdarlin Mikdarlin; Dilon Yosia Depari; Maulidia Meynisha Maharani; Khairani Khairani; Nur Adzkia Zuhro; Rio Septian Hardinata Hardinata (Cattleya Darmaya Fortuna, 2025)
The rapid growth in the use of e-money applications in society has provided convenience in conducting cashless transactions; however, it has also increased the risk of cybercrime, such as data theft, account hijacking, and digital identity misuse. Low levels of digital security literacy remain one of the main factors causing users to inadequately implement independent account protection measures. This community service activity aims to strengthen the digital security literacy of e-money users through the implementation of a two-factor authentication (2FA) system as an effort to enhance the security of digital transactions. The methods employed include digital security awareness sessions, training on the use of two-factor authentication in e-money applications, and direct assistance to participants during the activation and utilization of security features. The activity was conducted among groups of e-money users using a participatory approach. The results indicate an improvement in participants’ understanding of digital security risks as well as an increased ability to activate and utilize two-factor authentication systems in e-money applications. Furthermore, participants demonstrated more cautious and responsible behavior in maintaining the security of their digital accounts. This activity is expected to contribute to building public awareness and resilience against cybercrime threats and to support the development of a secure and sustainable digital transaction ecosystem.